A Study on Poultry Diseases in Kalaburagi Region: Prevalence, Causes, and Economic Impact (International Journal of Food and Nutritional Sciences, 2022)
Present study was conducted to investigate the health of poultry farms in the Kalaburagi region of India. The study collected primary data on infected birds and different diseases from the Government Veterinary Hospital, Kalaburagi, between 2022 and 2023. The researchers also collected secondary data from various poultry farms in the region. The study found that calcium deficiency, E-coli infection, and unabsorbed yolk infection were the most prevalent diseases in the area, and that environmental factors like temperature, parasitic diseases, and feeding deficiencies also affected the health of poultry birds. The research indicates that better sanitation and hygiene practices in poultry farms can help reduce the prevalence of diseases. Additionally, the study examined the profit and loss analysis of the farms. This study provides valuable insights into the health of poultry in the Kalaburagi region, and highlights the need for improved management practices to enhance the productivity and profitability of the poultry industry in the region.